2020
DOI: 10.3390/ijerph17124328
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Rehabilitation Improves Respiratory Muscle Function and Functional Capacity in Children with Congenital Heart Disease. A Prospective Cohort Study

Abstract: Critical surgical and medical advances have shifted the focus of congenital heart disease (CHD) patients from survival to achievement of a greater health-related quality of life (HRQoL). HRQoL is influenced, amongst other factors, by aerobic capacity and respiratory muscle strength, both of which are reduced in CHD patients. This study evaluates the influence of a cardiopulmonary rehabilitation program (CPRP) on respiratory muscle strength and functional capacity. Fifteen CHD patients, ages 12 to 16, with redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
14
1
3
Order By: Relevance
“…Even though some studies have measured the effect of a CPRP in children with CHD, very few have evaluated muscle function. Our group previously evaluated the benefits of cardiac training on respiratory muscle strength in this population, finding an improvement in the Maximum Static Inspiratory Pressure and the distance achieved in a 6 min walking test [27]. Other groups such as Moalla et al have observed a significant increase in the maximal voluntary contraction, despite being a home-based intervention [34].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though some studies have measured the effect of a CPRP in children with CHD, very few have evaluated muscle function. Our group previously evaluated the benefits of cardiac training on respiratory muscle strength in this population, finding an improvement in the Maximum Static Inspiratory Pressure and the distance achieved in a 6 min walking test [27]. Other groups such as Moalla et al have observed a significant increase in the maximal voluntary contraction, despite being a home-based intervention [34].…”
Section: Discussionmentioning
confidence: 88%
“…To complement the training and to provide the patient with a recreational component, the last sessions sporadically included virtual reality games. (d) Respiratory-training phase (20 min): as a final phase of muscular training, a respiratory musculature workout was performed using an Inspiratory Muscle Trainer Threshold (Respironics Respiratory Drug Delivery, Chichester, UK), working at least 30% of the subjects' Maximum Static Inspiratory Pressure [27]. (e) Cool-down phase (5 min): this included a light walk and body stretching.…”
Section: Interventionmentioning
confidence: 99%
“…Twelve articles assessed peripheral muscle strength 18,[26][27][28][29][30][31][32][33][34][35][36] and three assessed respiratory muscle strength. 5,8,37 The total sample size of the included studies was 1769. 5,8,18,[26][27][28][29][30][31][32][33][34][35][36][37] The studies comparing patients with CHD and healthy controls included 1202 participants in total, 27,33,34,36 and the studies only included patients with CHD had a total number of 567 participants.…”
Section: Resultsmentioning
confidence: 99%
“…5,8,37 The total sample size of the included studies was 1769. 5,8,18,[26][27][28][29][30][31][32][33][34][35][36][37] The studies comparing patients with CHD and healthy controls included 1202 participants in total, 27,33,34,36 and the studies only included patients with CHD had a total number of 567 participants. 5,8,18,26,[28][29][30][31][32]35,37 Regarding the studies with evaluation only of patients with CHD, the majority had undergone at least one surgical procedure and submitted it to cardiac training or rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation